Antidepressant Activity of Some Fractions of The Basil Leaves [Ocimum Basilicum (L)] on The Swiss Webster Male Mice - Hendy Suhendy; Muharam Priatna; Yedy Purwandi Sukmawan (Fakultas Farmasi Universitas Pancasila, 2018)
Objectives : Determine the antidepressant activity of some fractions of the leaves of Ocimum basilicum L Methods : The experimental methods are using Force Swimming Test and Tail Suspension Test. The experiment was divided into seven groups. Negative control group (CMC 1 %), Positive control group (fluoxetine 0,052 mg/20 g BW of mice), test I group (fraction of n-hexane 50 mg/Kg BW), test II group (fraction of ethyl acetate 50 mg/Kg BW), test III group (fraction of ethanol 50 mg/Kg BW), test IV group (combination of cyproheptadine 0,0208 mg/20 g BW of mice and fluoxetine 0,052 mg/20 g BW of mice) and test V group (combination of cyproheptadine 0,0208 mg/20 g BW of mice and fraction of ethyl acetate 50 mg/Kg BW). Result : The Force Swimming Test and Tail Suspension Test showed the same result that ethyl acetate fraction was given significant difference (p<0,05) in immobilization time reduction compared to negative control and has a better immobility reduction time than other groups. Added on cyproheptadine to fluoxetine and ethyl acetate fraction groups showed an increased in immobilization time compared to fluoxetine and ethyl acetate fraction alone. Conclusion : Ethyl acetate fraction showed better antidepressant activity than another fraction through the role of serotonin.